(untitled) (Third Sector Social Economic Review, 2014)
The work-family life conflicts caused by inability to balance work and family responsibilities and usually emerged with blocking transfer required time and interest for household roles because of work responsibilities, are closely associated with gender roles belonging to a particular time and place. The traditional gender roles, often attributed to women household responsibilities and care services, are an effective factor on women’s decision whether to participate in working life. It can be seen that perception of unequal gender leads to withdraw women from work life, especially when it merges with disadvantageous situations such as low income and/or low education. Because of this, women participate in work life have work-family conflicts more intensely than men. This article focus on that the effect of work-family life harmonization policies that included significantly in the social policy agenda of many European countries especially after the 1990s to transform unequal gender roles. In this context also the contribution of the current work-family life harmonization policies in Turkey to this effect will be tried to appreciate in the article.